Electronic payments in the public sector. - Thai, Veronica Ping. (2008)
The questionnaire sample collected was targeted at working professionals. The sample group should be computer-savvy and have access to the Internet. This group of customer’s will be located physically in Singapore. Therefore, the study will produce results pertaining mainly to the e-commerce activities in the government agencies of Singapore.